REGINE or “Gender Goes Legal in France” - Möschel, Mathias (Romanica Silesiana)
Like in other French scientific disciplines, gender has a hard time establishing itself as a legitimate approach in French legal studies. Nevertheless, whereas one can observe some changes occurring in social sciences and the humanities, French legal academy has been particularly impenetrable to feminist legal theory and gendered approaches to legal analysis. This article will first explain why this is the case and then describe how a new project, entitled REGINE, intends to address and overcome some of the obstacles. Key words: feminist legal theory, France, legal analysis, REGINE.<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />